Adoption of Safety Practices Against Occupational Hazards Among Building Construction Workers for Sustainable Development in Edo State, Nigeria - Itohan, Jane; Anavberokhai's, Musa O (UUM Press, 2021)
This study analyzed the safety practices followed by construction workers against occupational hazards to sustainable development in Edo State, Nigeria, using a descriptive research survey design. The analysis was motivated by three research questions and three null hypotheses. The study population consisted of 5,305 construction workers from 23 construction sites in the Oredo local government area of Edo State, Nigeria. The sample size of 530 respondents was selected for the analysis using a systematic random sampling technique that applied the Taro Yamane formula in drawing the sample size. The instrument used to collect data was a 10-item questionnaire built from the literature examined. The instrument has been tested by five experts. Spearman Brown rank correlation coefficient was used to determine the internal accuracy of the instrument and a correlation coefficient of.81 was obtained. In answering the research questions, the multiple regression statistics and the Pearson Product Moment Correlation was used to investigate the hypotheses at a.05 level of significance. The results of the study found, among other things, that the low use of safety practices among construction workers in the Oredo local government area of Edo State; a significant relationship between the use of safety practices and years of experience; a significant relationship between the use of safety practices and the level of education among construction workers. Based on the results of this report, it was suggested, among other things, that the management team of the various construction sites should demonstrate a greater commitment to the provision and compliance of safety equipment among workers to ensure optimal prevention of occupational hazards that will ensure sustainable growth.